2007
DOI: 10.1161/01.str.0000250742.61241.79
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Poly(ADP-Ribose) Polymerase Inhibitor to Suppress Inflammation and Neuronal Death After Cerebral Ischemia-Reperfusion

Abstract: Background and Purpose-Most stroke patients do not present for medical treatment until several hours after onset of brain ischemia. Consequently, neuroprotective strategies are required with comparably long therapeutic windows. Poly(ADPribose) polymerase inhibitors such as PJ34 are known to suppress microglial activation, a postischemic event that may contribute to neuronal death. We evaluated the effects of PJ34 administered 8 hours after transient forebrain ischemia. Methods-Rats were subjected to 10 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 47 publications
5
73
1
1
Order By: Relevance
“…Brains harvested at serial time points after forebrain ischemia showed microglial activation that was evident within 24 h and peaked approximately 3 days after ischemia (Figure 2A), consistent with prior reports (Hamby et al, 2007;Sugawara et al, 2002). Administration of the PARP inhibitor, PJ34, beginning 48 h after ischemia reduced microglial activation to basal levels within 24 h (Figure 2A and 2B).…”
Section: Delayed-onset Poly(adp-ribose) Polymerase Inhibition Reducessupporting
confidence: 87%
See 1 more Smart Citation
“…Brains harvested at serial time points after forebrain ischemia showed microglial activation that was evident within 24 h and peaked approximately 3 days after ischemia (Figure 2A), consistent with prior reports (Hamby et al, 2007;Sugawara et al, 2002). Administration of the PARP inhibitor, PJ34, beginning 48 h after ischemia reduced microglial activation to basal levels within 24 h (Figure 2A and 2B).…”
Section: Delayed-onset Poly(adp-ribose) Polymerase Inhibition Reducessupporting
confidence: 87%
“…Extensive activation of PARP-1 can promote cell death in ischemia and other conditions through a process involving NAD + depletion and mitochondrial release of apoptosis inducing factor (Jagtap and Szabo, 2005). By an entirely separate mechanism, PARP-1 may also contribute to injury after ischemia through its influence on the cellular inflammatory response (Hamby et al, 2007;Moroni, 2008;Oliver et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic inhibition of the canonical NF-κB pathway specifically in neurons has shown protective effect in focal ischemia models [37,38], and therefore, the neuroprotective effect seen in this study was likely due to direct modulation of cell death/survival pathways in neurons as suggested previously [23][24][25]. However, the inflammatory response can exacerbate neuronal death in the hippocampus [6][7][8][9]. Microglia undergoing the socalled M1-type pro-inflammatory activation can produce a number of cytotoxic mediators [39], and it has also been recently shown that microglia can phagocytose otherwise viable neurons and thus promote delayed neuronal death [10].…”
Section: Discussionsupporting
confidence: 67%
“…It is important, however, to place this approach in context. Although there is now strong evidence that the inflammatory response can exacerbate ischemic injury, [13][14][15][16][17][18] there is also evidence that some aspects of the inflammatory response are important for tissue repair. These aspects include phagocytosis of cell debris, remodeling of the extracellular matrix, and the release of cytokines and trophic factors.…”
Section: Introductionmentioning
confidence: 99%